Chapter 5 A Critical Analysis of Women’s Petitions and Gender Reform in Saudi Arabia - Jaber, Nora (University of Exeter Press, 2024)
Arabian Gulf, Persian Gulf, dissent, Gulf women’s petitions, Divorce in Gulf countries, Gulf women’s narratives, Women in Gulf media, Gulf women’s politics, gender reform in Saudi Arabia, Gulf societies